Are There Left–Right Differences in Ruptured Middle Cerebral Artery Bifurcation Aneurysms? A Single-Center Retrospective Study and Review of the Literature - Inamasu, Joji; Saito, Katsuya (Asian Journal of Neurosurgery, 2024)
Background The left (Lt) and right (Rt) middle cerebral artery bifurcation (MCAB) aneurysms have mostly been regarded as identical. Considering substantial Lt–Rt differences in hemispheric infarction, however, the presence of Lt–Rt differences may not be denied totally in patients with ruptured MCAB aneurysms. We herein investigated whether such Lt–Rt differences existed by a single-center retrospective study.Materials and Methods Clinical data prospectively acquired between 2011 and 2021 on 99 patients with ruptured MCAB aneurysms were analyzed. They were dichotomized based on the laterality, and demographic and outcome parameters were compared. Additionally, a literature review was conducted to elucidate possible Lt–Rt differences in the frequency of ruptured MCAB aneurysms (Rt/Lt ratio).Results Among the 99 patients, 42 had Lt and 57 had Rt ruptured MCAB aneurysms, with the Rt/Lt ratio of 1.36. Neither demographic, radiographic, nor outcome variables differed significantly between the two groups. A total of 19 studies providing information on the laterality of the ruptured MCAB were retrieved by literature search. A sum total for the Lt and Rt MCAB aneurysms was 671 and 940, making the Rt/Lt ratio of 1.40. After adding our data, a sum total for the Lt and Rt MCAB aneurysms was 713 and 997, making the Rt/Lt ratio of 1.40.Conclusion The Rt ruptured MCAB aneurysms were 1.40 times more frequent than the Lt-sided counterpart. While there may be some Lt–Rt differences in the MCA anatomy, it remains to be seen whether such anatomical differences are truly responsible for the disproportionately higher frequency of Rt MCAB aneurysms.
Keywords: middle cerebral artery; aneurysm; left–right differences; subarachnoid hemorrhage; frequency